MANAJEMEN PENGELOLAAN SUMBER DAYA ALAM (TENAGA UAP) PADA PT. PERTAMINA GEOTHERMAL ENERGY AREA LAHENDONG KOTA TOMOHON - MAMENTU, FERONICA TRISHA; LALOMA, ALDEN; LONDA, VERY (Sam Ratulangi University, 2020)
AbstractMany giant companies were initially very rapidly growing, but suddenly closed or broke. Indications of thecause of the company failed to operate its business one of them is Human error or human errors in carryingout management function. Based on the objective of this research is to know how the role of managementfunction of natural resources (steam power) in PT. Pertamina Geothermal Energy Area Lahendong KotaTomohon.Based on the problem formulation and in accordance with the objectives that want to be achieved in thisstudy then the type of research used in this research is qualitative descriptive research. Data collectiontechniques are conducted using observation, interviews, documentationBased on the results of the study with the interview method of several employees at PT. Pertamina GeotermalEnergy Area Lahendong found management of natural resources management at PT. PertaminaGeotermal Energy Area Lahendong seen from the process of planning has been working well that followsthe guidelines of the work that has been established including the implementation strategy, spatial design,and recruitment of personnel/employees. From the organizing process of people – people involved inmanagement management can be said to be good because all work in accordance with the field of theirduties – each with a clear division of work so that it has almost no obstacles as well as the timeliness ofmanagement work set strict discipline comes timely and also home according to the time prescribed for thosewho violate the rules are sanctioned until the dismissal Based on the results of the research found the factthat there is still abuse of power by managers where many employees were fired for unreasonable reasons.Keywords: management, management, natural resources